Dietary α-Linolenic Acid and Total ω-3 Fatty Acids Are Inversely Associated with Abdominal Aortic Calcification in Older Women, but Not in Older Men, 2. Issue 8 (3rd June 2015) - Shang, Xianwen; Sanders, Kerrie M; Scott, David; Khan, Belal; Hodge, Allison; Khan, Nayab; English, Dallas R; Giles, Graham G; Ebeling, Peter R
Abstract: Background: Associations of α-linolenic acid (ALA), eicosapentaenoic acid (EPA) plus decosahexaenoic acid (DHA), and total omega-3 (n–3) fatty acid (FA) intakes with abdominal aortic calcification (AAC) are not well understood. Objective: This study explored the associations between baseline and long-term changes in ω-3 FA consumption and AAC severity among community-dwelling older men and women. Methods: The present study used a subset of the Melbourne Collaborative Cohort Study in which participants were interviewed in 1990–1994 and again in 2010–2011. Dietary intake was evaluated at both baseline and follow-up with use of food-frequency questionnaires. AAC severity was assessed by both lateral thoraco-lumbar radiography and dual-energy X-ray absorptiometry (DXA) at follow-up. Results: A total of 312 participants aged 45–64 y old at baseline were followed for a duration of (mean ± SD) 18 ± 1 y. Baseline energy-adjusted ALA intake tended to be inversely associated with AAC severity by radiography [OR (95% CI) for tertile 3 vs. tertile 1: 0.49 (0.23, 1.02), P -trend: 0.06] and was inversely associated with AAC severity by DXA [OR (95% CI) for tertile 3 vs. tertile 1: 0.37 (0.16, 0.83)] in women, after adjustment for confounders. Women in the third tertile of total ω-3 FA intake had significantly lower AAC severity by radiography [OR (95% CI): 0.33 (0.16, 0.71)] and DXA [OR (95% CI): 0.27 (0.12, 0.62)] than those in the first tertile. Changes in tertile of ω-3 FA intake over 18 y were not found to be associated with AAC severity in either men or women. Conclusion: The results of our study suggest that dietary ALA and total ω-3 FA intakes are both important predictors of the development of AAC in older women, but not in older men.